Public Services at the Population and Civil Registration Office of Minahasa Regency - S. R. Siwij, Devie; B. Kairupan, Sisca; G. P. Gurning, Anderson (Indonesian Association for Public Administration (IAPA), 2023)
Registration of Minahasa Regency. The research method used is descriptive qualitative. The number of informants in this study were 5 people. Data collection uses observation, interview and documentation techniques. Data analysis through Data Reduction, Data Presentation and Drawing Conclusions. The results of the study show that the Public Service of the Department of Population and Civil Registration of Minahasa Regency is reviewed from 3 assessment indicators. in indicator 1). Service procedures for making E-ID cards are effective, both online and offline services, according to SOP 2). Inadequate facilities and infrastructure, or still not according to standards in terms of service time, employees have high discipline. 3). The competence of service delivery officers is reviewed after the completion time, there is a guarantee for completion time, but there are several internal and external factors that make the process of making this E-KTP hampered This study aims to describe the Public Services of the Department of Population and Civil, but for the entire service process, employees are always the intermediary in providing understanding and problem solver for every community who comes to get services in making E-KTP and also in the service process free of charge.